Occupation and adult onset of rhinitis in the general population. Issue 1 (30th July 2007) - Radon, K; Gerhardinger, U; Schulze, A; Zock, J-P; Norback, D; Toren, K; Jarvis, D; Held, L; Heinrich, J; Leynaert, B; Nowak, D; Kogevinas, M; et al.
Abstract : Objectives: Occupational exposures have been associated with an increased risk of new-onset rhinitis in apprentices. However, population-based prospective data are scarce and do not cover new onset of rhinitis later in life. The authors studied the association between occupational exposure and adult onset of rhinitis prospectively. Methods: The data of 4994 participants (age at follow-up 28–57 years) from 27 centres of the European Community Respiratory Health Survey II who were symptom-free at baseline were analysed. As outcome at follow-up self-reported (a) nasal allergies ("allergic rhinitis") and (b) runny, blocked nose for 12 months a year ("perennial rhinitis") were used. Occupational exposures at any time during follow-up were defined by job title. Results: The cumulative incidence of allergic rhinitis, perennial rhinitis and both conditions was 12%, 11% and 3%, respectively. Compared to office workers, male medical professionals were at increased risk of new onset of allergic rhinitis (OR 3.0; 95% CI 1.4 to 6.4). Odds ratios were reduced in metal workers not involved in metal making or treating (0.3; 95% CI 0.1 to 0.7). For perennial rhinitis ORs were significantly increased in cleaners (1.4; 95% CI 1.0 to 2.1). Conclusions: Cleaners and medical professionals may be at increased risk for adult-onset rhinitis.